(untitled) (Scientific journal of the Fergana State University, 2025)
This article focuses on the linguo-cultural analysis of “baptism” rituals in the German language, shedding light on their historical, religious, and social significance. Baptism, as one of the oldest Christian practices, symbolizes the spiritual union between humans and God. The article examines the Jewish roots of baptism and its establishment as a religious practice by Jesus. Drawing on studies by German linguists, it explores the historical development, symbolic meanings, and practical variations of baptism across different Christian denominations. The analysis highlights variations in practices: full immersion in Orthodox traditions, sprinkling or anointing the forehead with water in Catholicism, and emphasizing spiritual cleansing in Protestantism. Symbols such as water, white garments, the cross, and candles are interpreted for their religious and social importance. Today, baptism is noted not only as a religious rite but also as a significant social event. The differences between denominations, the role of baptism in social cohesion, and its modern reinterpretations suggest the need for further in-depth studies.